Using and implementing care bundles for patients with acute admission for COPD: qualitative study of healthcare professionals' experience in four hospitals in England. Issue 1 (25th March 2020) - Shaw, Ali; Morton, Katherine; King, Anna; Chalder, Melanie; Calvert, James; Jenkins, Sue; Purdy, Sarah
Abstract : Background: Care bundles are sets of evidence-based interventions to improve quality of hospital care at admission and discharge. Within a wider multi-method evaluation of care bundles for adults with an emergency admission for acute exacerbations of chronic obstructive pulmonary disease, a qualitative study was conducted. The aim was to evaluate how bundles were used, and healthcare professionals' experiences of the impact of bundles on the process of care delivery. Methods: Within the wider evaluation, four acute hospitals that were using COPD care bundles were purposefully sampled for geographical variation. Qualitative data were gathered through non-participant observation of patient care and interviews with healthcare professionals, patients and carers. This paper reports a thematic analysis of data from observation and interviews with professionals. Results: Healthcare professionals generally experienced care bundles as positive for standardising working practices and patient care, valuing how bundles could support a clear care pathway for patients, enable transitions between settings and identify postdischarge support required by patients. Successful use of bundles was perceived as more likely with the presence of either (or both) a clinical champion for bundles and system-based initiatives such as financial incentives, within a local culture of quality improvement. Challenges in accurately diagnosing COPD hampered bundle use, including delivery of bundles to those subsequently considered ineligible, or missed opportunities to deliver admission bundles to those with COPD. Conclusion: Care bundles shape admission and discharge care processes for patients with COPD, from the perspective of staff involved in their delivery. However, different organisational, staff and clinical factors aid or hinder bundle use in an acute hospital context, suggesting potentially resolvable reasons for variable implementation of bundles. Finally, bundles may enhance staff experience of care delivery, even if the impact on patient outcomes remains uncertain.